Numerical Simulation of Orthotic Insole Deformation for Diabetic Foot (Journal of Fiber Bioengineering and Informatics, 2015)
Custom-made orthotic insoles are routinely used in the treatment of the diabetic foot to reduce plantarpressure so as to minimise the risk of neuropathic ulceration. Due to the 3D geometry shape of the footand insole, the measurement of the foot-orthosis interface pressure at different plantar regions in relationto insole material fabrication is vital for effective foot orthotic treatment. In the present study, a model ofa custom-made three-layer contoured insole that simulates foot-insole interactions is developed by usingfinite element analysis. With the use of the insole material properties and plantar pressure distributionduring balanced standing as the inputs, the magnitude of the deformity and the compressive stressdistributed across the regions of the insole made of different combinations of materials are simulated.After validation, the simulated deformation shows good agreement with the result obtained by imageprocessing technology. The simulation model not only provides a promising solution to the modificationof materials for insoles by predicting and visualising insole deformation patterns, but also effectivelyoptimises the design and development process of orthotic insoles without the need to fabricate and testthe insoles in a series of wear trials.